Occurrence of periodontopathic and superinfecting bacteria in chronic and aggressive periodontitis subjects in a Colombian population (2007)
Differences in the composition of subgingival microbiota in periodontitis have been observed in different geographic locations. Some of these microbial differences could have clinical significance. This study describes clinical parameters and the composition of the subgingival microbiota in chronic periodontitis (CP) and aggressive periodontitis (AgP) patients in a Colombian population. Clinical parameters (probing depth, clinical attachment level, bleeding on probing, and plaque index) and plaque samples from 68 CP, 12 AgP, and 30 periodontally healthy subjects were analyzed. Subgingival samples were processed using culture, biochemical tests, and polymerase chain reaction for the detection of periodontal and superinfecting pathogens. The analysis of variance, χ2, and Kruskal‐Wallis tests were used to evaluate differences between groups for clinical parameters and microbiologic composition (P ≤0.05). Clinical parameters were significantly increased in CP and AgP patients compared to healthy subjects (P <0.001), but no differences were found between periodontitis groups. Porphyromonas gingivalis, Tannerella forsythensis, and Eikenella corrodens showed higher frequencies in AgP compared to CP and healthy subjects (P <0.05). Extension (localized and generalized) of the periodontal destruction had no effect on the composition of the subgingival microbiota. Gram‐negative enteric rods were more frequent in AgP patients (P <0.01). This study demonstrated a high prevalence of P. gingivalis, T. forsythensis, and E. corrodens in AgP patients. Gram‐negative enteric rods were frequent in AgP and CP patients. Differences in the composition of subgingival microbiota in periodontitis patients need to be taken into account when considering the best therapeutic approach for each individual, including the use of antibiotics.